Penerapan Metode Agile Development dalam Rancang Bangun Single Sign-On pada Sistem Informasi Akademik - Sandi Agung; Alek Wijaya; Jemakmun Jemakmun; Firamon Syakti (Pusat Riset dan Inovasi Nasional, 2025)
In today's digital era, educational institutions face challenges in managing various academic information systems that require separate authentication for users. This often causes difficulties in accessing various applications with different logins. This study aims to develop and implement Single Sign-On in the academic information system of SMP Dharma Bhakti Palembang using the Agile Development method. Agile Development was chosen because of its iterative approach that allows flexibility in system development and improvement based on user feedback. System testing was conducted using the Black Box Testing method, which focuses on testing system functionality based on input and output without considering the internal structure of the code. This testing includes user authentication validation and SSO integration with various academic applications. The results of the study indicate that the implementation of SSO can simplify the user authentication process and reduce the risk of login errors. Thus, this study provides an innovative solution that can be a reference for other educational institutions in developing more integrated academic information systems.